Analysis of Budget Flexibility for the Program of Improving Competence and Professionalism of Madrasah Teachers at the Ministry of Religious Affairs Regional Office for DKI Jakarta Province - Dian Retno Kencono; Nurliah Nurdin; R Luki Kurnia (UIN Raden Mas Said Surakarta, 2022)
Refocusing strategy has become one of the fiscal policies adopted by the government when the COVID-19 pandemic hit Indonesia. This strategy involves reallocating the budget from personnel, goods, and capital expenditures to fund the National Economic Recovery Program. However, the implementation of this policy, without adequate preparation, can have performance implications. This research addresses the challenges related to the dynamic and adaptive state budget during a crisis. The method used is a case study based on facts, which is then analyzed using the theory of Budgeting Flexibility, considering three inseparable aspects in achieving budget flexibility: agreement on purposes, mutual commitment between parties, and creating agile organizations. Therefore, Refocusing does not compromise the performance of executing tasks and functions in supporting the implementation of programs aimed at improving the professionalism of teachers in Madrasah education. This research will serve as the basis for policymakers in budget implementation across all levels in the Ministry of Religious Affairs Regional Office for DKI Jakarta Province.